2020
DOI: 10.3390/w12102871
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Biochar and Pyrolysed Materials to Improve Water Quality through Microcystin Sorption Separation

Abstract: Harmful algal blooms have increased globally with warming of aquatic environments and increased eutrophication. Proliferation of cyanobacteria (blue-green algae) and the subsequent flux of toxic extracellular microcystins present threats to public and ecosystem health and challenges for remediation and management. Although methods exist, there is currently a need for more environmentally friendly and economically and technologically feasible sorbents. Biochar has been proposed in this regard because of its hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 118 publications
1
21
0
Order By: Relevance
“…This is likely due to the higher aromatic content in FSHA than in MC-LR that competes with MC-LR for the binding sites on BC via π–π interactions . Furthermore, FSHA (average molar mass 39.098 kDa) can also block BC mesopores to hinder the adsorption of MC-LR (∼1 kDa) by BC. ,, Therefore, the presence of FSHA negatively impacted the two major driving forces of MC-LR adsorption by BC (π–π interactions and mesopore filling) . Coating PDDA hydrogel on BC also reduced the mesopore volume (from 0.055 to 0.027 cm 3 /g as shown in Figure S2) but introduced new functional groups to the adsorbent, consequently altered the mechanisms of MC-LR adsorption from pore-filling to chemical attractions, and overcame the drawbacks of BC for MC-LR adsorption in the presence of FSHA.…”
Section: Resultsmentioning
confidence: 99%
“…This is likely due to the higher aromatic content in FSHA than in MC-LR that competes with MC-LR for the binding sites on BC via π–π interactions . Furthermore, FSHA (average molar mass 39.098 kDa) can also block BC mesopores to hinder the adsorption of MC-LR (∼1 kDa) by BC. ,, Therefore, the presence of FSHA negatively impacted the two major driving forces of MC-LR adsorption by BC (π–π interactions and mesopore filling) . Coating PDDA hydrogel on BC also reduced the mesopore volume (from 0.055 to 0.027 cm 3 /g as shown in Figure S2) but introduced new functional groups to the adsorbent, consequently altered the mechanisms of MC-LR adsorption from pore-filling to chemical attractions, and overcame the drawbacks of BC for MC-LR adsorption in the presence of FSHA.…”
Section: Resultsmentioning
confidence: 99%
“…Techniques used for water filtration to remove harmful compounds, such as cyanobacteria and cyanotoxins, include activated carbon filtration, clay-like silica material, adsorption, biologically active sand filtration, and membrane filtration. In most cases, these techniques are preceded by coagulation-flocculation processes [89][90][91][92][93][94].…”
Section: Filtration and Complexationmentioning
confidence: 99%
“…For instance, it was reported that there is strong proton adsorption in the case of the presence of several hydroxyl or phenolic groups under certain pH conditions [95,97,100]. Activated carbon may derive from different materials, namely wood, coal, coconut shells, or peat [75,92,[101][102][103]. Notwithstanding, Albuquerque et al [102] related the existence of MC-LR adsorption differences even among types of woods from which charcoal can be made; therefore, a wise choice of the sample of wood to be used has been made to maximize adsorption.…”
Section: Filtration and Complexationmentioning
confidence: 99%
“…These techniques rely on the removal of whole cells and are not as effective against the free microcystins released upon cell lysis . Sand filtration is another commonly used water treatment technique, which can effectively remove up to 94% of microcystins under optimal conditions. , However, reductions in temperature to 0–10 °C have been found to greatly reduce efficiency, with only 43% microcystin removal reported. Sand filtration also relies on long water residing times of 2–6 months for optimal microcystin removal, which is not always feasible; therefore, rapid sand filtration methods with reduced residing times are often employed.…”
Section: Introductionmentioning
confidence: 99%
“…In conjunction with the aforementioned water treatment methods, additional disinfection processes such as chlorination, ozone, or activated carbon may be employed. Chlorination has been shown to remove up to 99% of microcystin in lab-scale studies, however, the formation of undesirable toxic byproducts is problematic. , Ozone treatment of drinking water can effectively remove microcystins; however, the process requires close monitoring as the amount of ozone required to achieve this varies depending on the water quality. , Combination of these methods with UV irradiation has been shown to improve their efficacy. , …”
Section: Introductionmentioning
confidence: 99%